Property Rights in the Focus of Social Theories:Through Breaking Boundaries towards Interdisciplinary - Maria Sakaeva (Journal of Economic Sociology, 2016)
This article includes the main social theories of property rights. The question about the existence and development of property right institution is discussed from three persepctives: economic, sociological, and interdisciplinary. Special attention is given to a new institutional school with D. North as a head. In the 21st century, a wave of sociological and anthropological critics showed that institutional scholars’ views of property rights were not relevant, which caused an interdisciplinary turn. It was not easy for sociologists to prove their interest in property rights. While political economists were interested in the state’s role in property protection, new institutional economists focused on the institutionalization of property, and social anthropologists researched cultural roots in property relations. Finally, liberal economists’ normative and ideal views of property rights were weakened. Sociologists argue that property is not restricted to economic sphere, that it depends on and influences culture and law, state and society, collective and individual. The list of property types was enlarged due to recent sociological studies. For example, the female body and trademark were both discussed in terms of property. The first part of the article reviews notions of “property” and “property rights” and a deconstruction of “property” by sociologists. The second part deals with the state’s role in the development of private property and the problem of property protection, discussed within the frameworks of new institutionalism. Then the article examines economic and sociological concepts, which explain why culture matters for property relations, and the article describes the diversity of property relations in practice. Finally, ways of protecting property rights under the institutional instability are analyzed.